Libya : Staff Report For The 2013 Article Iv Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
The political and security environment remains uncertain in Libya. Libya faces the challenges of stabilizing the economy and responding to the aspirations of the revolution. The near-term outlook is favorable, but there are significant risks. The overarching policy objective should be to foster inclusive growth. Banks are not intermediating, and resources should be devoted to its effective implementation. Expenditure is skewed toward wages and subsidies. Libya needs to adopt a comprehensive reform strategy. The government agrees with the assessment of the economic outlook and associated risks and policy options as outlined by Executive Directors.